IMPLEMENTASI PERDA KOTA PADANG NOMOR 2 TAHUN 2013 TENTANG PENANGGULANGAN KEMISKINAN DAN PENINGKATAN KESEJAHTERAAN OLEH DINAS SOSIAL KOTA PADANG - Yesi Ermaini Simamora; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Poverty alleviation is a policy of the central and regional government programs that are carried out systematically, planned and synergized with the business community and the community to reduce the number of poor people in order to improve the welfare of the community. This study aims to determine the Implementation of Regional Regulation Number 2 of 2013 concerning Poverty Reduction and Welfare Improvement by the Social Service in Koto Tangah Subdistrict, Padang City. This research is motivated by the implementation of poverty alleviation is not right on target. There are still many poor people, especially in the District of Koto Tangah and lack of awareness of people who claim to be poor. This research is descriptive with a qualitative approach. Informants were determined by purposive sampling and random. Data is collected through interviews, observation and documentation. The results of this study showed that the implementation of poverty reduction program policies that have not been effective.